Comparison Between On‐Demand Dosing of Dapoxetine Alone and Dapoxetine Plus Mirodenafil in Patients with Lifelong Premature Ejaculation: Prospective, Randomized, Double‐Blind, Placebo‐Controlled, Multicenter Study. (12th August 2013) - Lee, Won Ki; Lee, Seong Ho; Cho, Sung Tae; Lee, Yong Sung; Oh, Cheol Young; Yoo, Changhee; Cho, Jin Seon; Lee, Sang Kon; Yang, Dae Yul
Abstract: Introduction: There is partial evidence to support the use of phophodiesterase‐5 inhibitor (PDE5‐I) for the treatment of premature ejaculation (PE). Aim: We compared on‐demand dosing of dapoxetine alone and combined with mirodenafil in subjects with lifelong PE and without erectile dysfunction (ED). Methods: Our prospective, randomized, double‐blind, placebo‐controlled, multicenter trial enrolled 118 subjects with lifelong PE without ED. PE was diagnosed using D iagnostic and S tatistical M anual of M ental D isorders, fourth edition, text revision. Patients were divided into two groups: dapoxetine 30 mg plus placebo (group A, n = 56) and dapoxetine 30 mg plus mirodenafil 50 mg (group B, n = 62). Main Outcome Measures: During 12 weeks, intravaginal ejaculatory latency time (IELT) and the time from foreplay to beginning intercourse (FTIT) with a stopwatch, and Premature Ejaculation Profile (PEP) were measured. Overall sexual act time (OSAT; sum of FTIT and IELT) was calculated. Any treatment‐emergent adverse events (TEAEs) were also recorded. Results: Over 12 weeks, IELT, OSAT, and PEP index score significantly improved in group B compared with group A (increased geometric mean IELT in group A and B = 3.6 and 6.1 minutes, P = 0.026; increased geometric mean OSAT in group A and B = 5.5 and 9.9 minutes, P = 0.012; increased median PEP index score in group A and B = 1.0 and 1.3, P = 0.046). However, there was no significant difference between two groups with respect to improvement of FTIT ( P = 0.147). TEAEs did not differ between groups (all P > 0.05), and there was no serious adverse event in any subjects. Conclusions: Low dose of dapoxetine combined with mirodenafil showed better results in terms of IELT, OSAT, and PEP index score, and similar TEAEs, compared with that of dapoxetine only. Our results support the suggestion that the PDE5‐Is have a potential role in the treatment of PE without ED.Lee WK, Lee SH, Cho ST, Lee YS, Oh CY, Yoo C, Cho JS, Lee SK, and Yang DY. Comparison between on‐demand dosing of dapoxetine alone and dapoxetine plus mirodenafil in patients with lifelong premature ejaculation: Prospective, randomized, double‐blind, placebo‐controlled, multicenter study. J Sex Med 2013;10:2832–2841.